2009
DOI: 10.1542/peds.2008-0231
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Vaccine Coverage for Low Birth Weight Infants During the First Year of Life in a Large Managed Care Population

Abstract: Despite recommendations that lower birth weight infants be vaccinated as the same chronological age as normal birth weight infants, extremely low birth weight and very low birth weight infants are immunized at significantly lower rates relative to low birth weight and normal birth weight infants at 2, 4, and 6 months of age. However, by 12 months of age this finding persists only in extremely low birth weight infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 37 publications
2
43
1
2
Order By: Relevance
“…Studies conducted in developed countries have obtained similar results (11-14). Langkamp et al found that low birth-weight infants received the first two doses of polio and the first three doses of DPT at significantly older ages than normal birth-weight infants (12).…”
Section: Discusionsupporting
confidence: 64%
See 4 more Smart Citations
“…Studies conducted in developed countries have obtained similar results (11-14). Langkamp et al found that low birth-weight infants received the first two doses of polio and the first three doses of DPT at significantly older ages than normal birth-weight infants (12).…”
Section: Discusionsupporting
confidence: 64%
“…However, when considering only VLBW infants the immunization levels were significantly lower than normal birth-weight infants (14). This delay is more pronounced during the first year of life and reduced after this (11,12,14). Extremely-low-birth-weight infants are the exception since they continue to receive immunizations at significantly higher ages after 12 months (14).…”
Section: Discusionmentioning
confidence: 96%
See 3 more Smart Citations